Functional Significance of Satellite DNAs: Insights From Drosophila - Shatskikh, Aleksei S.; Kotov, Alexei A.; Adashev, Vladimir E.; Bazylev, Sergei S.; Olenina, Ludmila V. (Frontiers in Cell and Developmental Biology, 2020)
Since their discovery more than 60 years ago, satellite repeats are still one of the most enigmatic parts of eukaryotic genomes. Being noncoding DNA, satellites were earlier considered to be non-functional "junk", but recently this concept has been extensively revised. Satellite DNA contributes to the essential processes of formation of crucial chromosome structures, heterochromatin establishment, dosage compensation, reproductive isolation, genome stability and development. Genomic abundance of satellites is under stabilizing selection owing of their role in the maintenance of vital regions of the genome – centromeres, pericentromeric regions, and telomeres. Many satellites are transcribed with the generation of long or small non-coding RNAs. Misregulation of their expression is found to lead to various defects in the maintenance of genomic architecture, chromosome segregation and gametogenesis. This review summarizes our current knowledge concerning satellite functions, the mechanisms of regulation and evolution of satellites, focusing on recent findings in Drosophila. We discuss here experimental and bioinformatics data obtained in Drosophila in recent years, suggesting relevance of our analysis to a wide range of eukaryotic organisms.